Low complexity receiver of sparse code multiple access based on dynamic trellis. Issue 9 (1st June 2020) - Peng, Xiaohuan; Pan, Zhipeng; Lai, Ke; Wen, Lei; Lei, Jing
Abstract : Sparse code multiple access (SCMA) is one of the non‐orthogonal multiple access schemes to meet the demands of massive connection and high spectral efficiency in the 5G communications. Since the sparsity of the codebook, the message passing algorithm (MPA) can be utilised for multi‐user detection. However, the high computational complexity of MPA hinders the practical application of SCMA. The extended Max‐Log MPA (EML‐MPA) and the channel‐adaptive extended Max‐Log MPA (CAD‐EML‐MPA) help to reduce the complexity of conventional Log‐MPA with trellis representation. On this basis, the authors propose a dynamic trellis based MPA (DT‐MPA) in this study. DT‐MPA selects symbols dynamically according to a specific threshold τ in each iteration of MPA. The impact of the threshold on the complexity and convergence behaviour is analysed. Simulation results show that the DT‐MPA with variable τ which is related to bit signal‐to‐noise can achieve better bit error rate performance and lower complexity than EML‐MPA and CAD‐EML‐MPA.